Pengaruh Profitabilitas, Likuiditas dan Leverage terhadap Nilai Perusahaan dengan Kebijakan Dividen Sebagai Variabel Moderasi - Herlin Trikasih Putri; Ingra Sovita (Jurnal Ekonomi dan Bisnis Digital, 2022)
This study aims to determine and analyze the effect of profitability, liquidity and leverage on firm value with dividend policy as a moderating variable in manufacturing companies in the consumer goods industry sub-sector for the 2018-2021 period. The approach uses a quantitative approach. The population in this study were 80 manufacturing companies in the consumer goods industry sub-sector which were listed on the Indonesia Stock Exchange for the 2018-2021 period. The sample selection technique used the purposive sampling method and produced a sample of 24 manufacturing companies in the consumer goods industry sub-sector which were listed on the Indonesia Stock Exchange for the 2018-2021 period. The data analysis used is multiple linear regression and MRA (Moderated Regression Analysis) using SPSS version 25 software. The results show that profitability and leverage have a positive effect on firm value, while liquidity has no effect on firm value, dividend policy is able to moderate the effect of profitability and leverage on company value, while dividend policy is unable to moderate the effect of liquidity on the value of manufacturing companies in the consumer goods industry sub-sector for the 2018-2021 period.